KONTRIBUSI KELENTUKAN PINGGANG DAN EXSPLOSIVE POWER OTOT TUNGKAI TERHADAP AKURASI SHOOTING PEMAIN SEPAKBOLA - -, Zulbahri (Universitas Pasir Pengaraian, 2015)
The problems of this study was the low of Soccer Player’s Shooting Accuracy.This study aimed to determine the contribution of flexibility of waist, the exsplosive power of limbs muscle, and both of them toward soccer player’s shooting accuracy in SMKN 8 Padang. The population was 25 soccer players in SMKN 8 Padang and all of them became the samples because of using total sampling technique. Data collection was performed by measuring the flexibility of waist with flexiometer, the explosives power of limb muscle with standing broad jump and shooting accuracy with shooting on target. A simple correlation analysis and multiple correlation analysis techniques with significance level á = 0.05 were used to analyse the data and test the research hypothesis. The formula r 2 x 100% was used to know the contribution. The result showed (1) flexibility of waist contributed to the shooting accuracy of 37.6%, (2) limb muscle explosives power contributes to the shooting accuracy of 45.6% (3) flexibility of waist and limb muscle explosives power contributed jointly to the shootingaccuracy of 54.3%.